(untitled) (Huellas, 2021)
Since the crisis with the agriculture and livestock sector, which took place in the late 1990s and early 2000s, various state and non-state actors have tried to stimulate, socially and economically, rural towns in Argentina. In this context, tourism is becoming increasingly frequent in initiatives and programs as a revitalization strategy, considering its positive aspects. However, the tourism development process entails a number of material and symbolic transformations that can provoke tensions. Hence, in this article we propose to critically analyze how these processes are generated through the construction of a “cultural biography”. This proposal allows us to investigate and contextualize the implications of tourism in rural towns.